Total synthesis of (+/-)-1,3,4,5-tetragalloylapiitol - Patel, Ramesh M.; N. P. Argade (Synthesis-Stuttgart, 2009)
Starting from citraconic anhydride, the first total synthesis of (+/-)-1,3,4,5-tetragalloylapiitol has been demonstrated via a stepwise route involving generation of an apiitol derivative followed by benzoylation.
Keywords: (+/-)-1; 3; 4; 5-tetragalloylapiitol; allylic hydroxylation; Natural products; osmium tetroxide